Sexually Transmitted Infections Prevalence and Cascade of Care among Undocumented Sex Workers: A Twenty-Year-Long Experience - Alessandra Donisi; Agnese Colpani; Beatrice Zauli; Andrea De Vito; Vito Fiore; Sergio Babudieri; Giordano Madeddu (Life, 2023)
Undocumented migrant sex-workers (SW) are vulnerable to Sexually Transmitted Infections (STIs). However, data regarding prevalence and linkage-to-care are lacking. Defining epidemiology is crucial to implement preventive measures. We report data from SW attending a facility for migrants in Piacenza, Italy. We collected medical records from 1999 until 2021. Quantitative variables were summarized as mean and standard deviation (SD), and qualitative ones by absolute and relative frequencies. Logistic regression analysis was performed to assess the relationship between sociodemographic, clinical variables, positive testing, and loss to follow-up (LFU). Overall, 1035 STI episodes were collected, 917 in cisgender-females (CF), and 118 in transgender-females (TF). Overall, 474 diagnoses were made. Three-hundred-ninety-two/474 (82.7%) started therapy, and 264/474 (55.7%) complied with a follow-up. Only 51.5% of HBV and 30.8% of HIV were linked to care. Having symptoms (OR 1.70 (95% CI 1.06–2.73), p = 0.028) and previous STIs (OR 1.36 (95% CI 1.04–1.77), p = 0.022) were associated with a higher chance of STIs, while at-risk intercourse to lower risk (OR 0.19 (95% CI 0.07–0.49), p = 0.001). TF had higher odds of bloodborne infections and syphilis (OR 2.61 (95% CI 1.17–5.80), p = 0.019). Regarding follow-up, the older the patient, the higher the LFU (OR 1.05 (95% CI 1.01–1.10), p = 0.021). Our data showed a high prevalence of STIs and LFU among undocumented SW. TF are even more vulnerable. Further efforts should be put into targeted interventions.